Analytic Approximations of Scattering Effects on Beam Chromaticity in 21‐cm Global Experiments. Issue 12 (12th December 2022) - Rogers, Alan E. E.; Barrett, John P.; Bowman, Judd D.; Cappallo, Rigel; Lonsdale, Colin J.; Mahesh, Nivedita; Monsalve, Raul A.; Murray, Steven G.; Sims, Peter H.
Abstract: Scattering from objects near an antenna produce correlated signals from strong compact radio sources in a manner similar to those used by the "Sea Interferometer" to measure the radio source positions using the fine frequency structure in the total power spectrum of a single antenna. These fringes or ripples due to correlated signal interference are present at a low level in the spectrum of any single antenna and are a major source of systematics in systems used to measure the global redshifted 21‐cm signal from the early universe. In the Sea Interferometer a single antenna on a cliff above the sea is used to add the signal from the direct path to the signal from the path reflected from the sea thereby forming an interferometer. This was used for mapping radio sources with a single antenna by Bolton and Slee in the 1950s. In this paper we derive analytic expressions to determine the level of these ripples and compare these results in a few simple cases with electromagnetic modeling software to verify that the analytic calculations are sufficient to obtain the magnitude of the scattering effects on the measurements of the global 21‐cm signal. These analytic calculations are needed to evaluate the magnitude of the effects in cases that are either too complex or take too much time to be modeled using software. Key Points: In order to accurately measure the spectrum of the radio sky the antenna beam needs to be smooth without frequency structure The beam of the antenna on its ground plane is influenced by the scatter from nearby objects which produces ripples in the spectrum Analytic expressions provide an estimate of the scatter in an environment too complex for accurate electromagnetic modeling of the beam